APPLICATION OF CURVILINEAR GRID IN 3E HYDRODYNAMICS MODEL : Abstract - Berlianty NIM. 224 03 011, Dessy
Abstract: Finite difference hydrodynamic models of sinuous open channels, such as estuary or coastal waters with complex geometry, require curvilinier grid system. Cartesian models with rectangular or square grid cells are simple to apply, but require large number cells, as the cell size is determined bay cross-stream resolution. This study presents a curviliniear approach suitable for hydrodynamic model of coastal or open channel system with sinuous geometry. The approach has been employed into horizontal grid system of the 3D Princeton Ocean Model (POM). Further, the 3D hudrodynamic model with horizontal curvilinear coordinate was utilized to simulate wind driven currents in simple synthetic channels with sinuous geometry. Analytic calculations were then carried out to verify the simulation results.